PENGARUH HUTANG JANGKA PANJANG, HUTANG JANGKA PENDEK DAN MODAL KERJA TERHADAP PROFITABILITAS PADA PT DELTA ATLANTIC INDAH MEDAN (PERIODE 2013-2017) - REBECCA EVADINE (LP2MTBM MAKARIOZ, 2019)
In carrying out its operations PT Delta Atlantic Indah Medan has the main objective of maximizing assets for the owner of the company or its shareholders. How to increase the profitability of company is always be a major concern for business owners, corporate management, investor or prospective creditors. The research purpose of this is to know and analyze the effect of long-term debt, short-term debt and working capital on profitability at PT Delta Atlantic Indah Medan. The method used in this research is analysis method descriptive. Analysis data method that we used is multiple linear regression by using SPSS software. The results show long-term debt, short-term debt and working capital simultaneously have a positive and significant impact on profitability at PT Delta Atlantic Indah Medan